The unintended long-run impacts of agro-terrorism in Brazil - Yuri Barreto; Rodrigo Carvalho Oliveira (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2022)
This paper studies the unintended long-run effects of a permanent agricultural shock led by agro-terrorism in Brazil on the education and labour market. We explore the witches' broom outbreak in cocoa farms in the world's second most important cocoa production region until 1989, the southeast of Bahia state in the northeast of Brazil. Although the introduction of the disease had political motivations, it had unintended effects on poor people's lives. To assess the impact of the witches' broom disease, we leverage information about people born in municipalities affected and not affected by the disease and explore the difference in educational attainments between cohorts older and younger than 18 years old at the time of the witches' broom outbreak. The main results show that the witches' broom outbreak negatively impacted the long-term education and earnings of individuals living in affected municipalities. We show a piece of evidence that the increase in child labour may drive our results. The negative effects on young cohorts are consistent with the known relation between child labour and cocoa production and the literature about the long-term effects of economic shocks.
Keywords: N36; O12; O15; 330; witches' broom; Brazil; education; wages